2019
DOI: 10.3390/ma12010159
|View full text |Cite
|
Sign up to set email alerts
|

Lignin as a Functional Green Coating on Carbon Fiber Surface to Improve Interfacial Adhesion in Carbon Fiber Reinforced Polymers

Abstract: While intensive efforts are made to prepare carbon fiber reinforced plastics from renewable sources, less emphasis is directed towards elaborating green approaches for carbon fiber surface modification to improve the interfacial adhesion in these composites. In this study, we covalently attach lignin, a renewable feedstock, to a graphitic surface for the first time. The covalent bond is established via aromatic anchoring groups with amine functions taking part in a nucleophilic displacement reaction with a tos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…In this context, the presence of O, N and H in the CFs is associated with the existence of surface functional groups (-C-H; -C-OH; -C-O-C; -C=O; C=N; -COOH; etc. ), the number of which decreases with subsequent heat treatments at a higher temperature [33,43,45,[65][66][67][68][69]. Thus, the B-O results correlate well with the Raman analysis, where the carbonised CFs spectra showed broad and intense D 1 , D 4 and D 3 bands, indicating a significant number of heteroatoms and aliphatic side chains.…”
Section: Chemical Stability Of Cfs In Lioh With Regard To Their Strucsupporting
confidence: 72%
“…In this context, the presence of O, N and H in the CFs is associated with the existence of surface functional groups (-C-H; -C-OH; -C-O-C; -C=O; C=N; -COOH; etc. ), the number of which decreases with subsequent heat treatments at a higher temperature [33,43,45,[65][66][67][68][69]. Thus, the B-O results correlate well with the Raman analysis, where the carbonised CFs spectra showed broad and intense D 1 , D 4 and D 3 bands, indicating a significant number of heteroatoms and aliphatic side chains.…”
Section: Chemical Stability Of Cfs In Lioh With Regard To Their Strucsupporting
confidence: 72%
“…Recent advances achieved in our laboratory hold promise for deriving thermoplastic cellulose derivatives from biomasses (Kakuchi et al, 2017; Suzuki et al, 2018), and utilizing these materials for preparing short carbon fiber reinforced plastics (Szabó et al, 2019a). We have also shown that the adhesion between the cellulosic matrix and carbon fiber can be improved by modifying the carbon fiber surface (Szabó et al, 2018a,b, 2019b). It appeared that immobilizing lignin on carbon fiber surface leads to a great enhancement in interfacial properties due to secondary interactions between lignin and the polymer matrix (Szabó et al, 2019b).…”
Section: Introductionmentioning
confidence: 98%
“…We have also shown that the adhesion between the cellulosic matrix and carbon fiber can be improved by modifying the carbon fiber surface (Szabó et al, 2018a,b, 2019b). It appeared that immobilizing lignin on carbon fiber surface leads to a great enhancement in interfacial properties due to secondary interactions between lignin and the polymer matrix (Szabó et al, 2019b). It follows that lignin can serve as a functional material to improve the interfacial interactions in green biobased composites.…”
Section: Introductionmentioning
confidence: 98%
“…Microdroplets on single CFs were prepared using polymer melts similar to others, 64 and in line with our previous report. 44 Briefly, CP was kept on a hot plate at 235 °C for 5 min, whereupon a single fiber was gently immersed into the melt and then transferred to another plate heated to 250 °C (3 min treatment time). Upon cooling to room temperature, the formation of separated microdroplets could be confirmed.…”
Section: Methodsmentioning
confidence: 99%